Krisis Pendidikan Pengungsi : Upaya UNICEF dalam Penyebaran Norma Hak Pendidikan terhadap Anak-Anak Pengungsi Rohingya di Bangladesh - Luthfi Marisa Dewi; Reni Windiani; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The educational crisis experienced by Rohingya refugee children in Bangladesh became even more difficult when a new flow of refugees arrived in 2017. The Bangladeshi government did not pay more attention towards the crisis, putting it into the international spotlight and causing UNICEF as an international organization to attempt and solve the problem. The purpose of this study is to explain UNICEF's attempt in spreading the norms of children's education rights towards the refugee children in Bangladesh. This study will use three concepts of conceptual thinking, namely the concept of Norm Diffusion, the concept of International Organization and the concept of Humanitarian Action with qualitative research methods and descriptive analytical research types. The results of the study show that UNICEF attempts to spread the norms of the right to education for Rohingya refugee children through a number of different programs, such as the launch of the LCFA program, the launch of the Myanmar curriculum in 2020 in collaboration with the Bangladesh government for the education of Rohingya refugee children.